2020
DOI: 10.3390/cells9061433
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Molecular Basis of Phosphoantigen Recognition by Vγ9Vδ2 T Cells

Abstract: About 1–5% of human blood T cells are Vγ9Vδ2 T cells. Their hallmark is the expression of T cell antigen receptors (TCR) whose γ-chains contain a rearrangement of Vγ9 with JP (TRGV9JP or Vγ2Jγ1.2) and are paired with Vδ2 (TRDV2)-containing δ-chains. These TCRs respond to phosphoantigens (PAg) such as (E)-4-hydroxy-3-methyl-but-2-enyl pyrophosphate (HMBPP), which is found in many pathogens, and isopentenyl pyrophosphate (IPP), which accumulates in certain tumors or cells treated with aminobisphosphonates such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 101 publications
(255 reference statements)
0
53
0
Order By: Relevance
“… 25 , 31 Importantly, recent insights revealed that the agonistic activity of mAb 20.1 also depended on cell surface-expressed BTN2A1. 35 The currently discussed model 38 of Vγδ2 T cell activation and the role of BTN molecules and pAgs are illustrated in Fig. 1 .…”
Section: Ligand Recognition By Human γδ T Cellsmentioning
confidence: 99%
“… 25 , 31 Importantly, recent insights revealed that the agonistic activity of mAb 20.1 also depended on cell surface-expressed BTN2A1. 35 The currently discussed model 38 of Vγδ2 T cell activation and the role of BTN molecules and pAgs are illustrated in Fig. 1 .…”
Section: Ligand Recognition By Human γδ T Cellsmentioning
confidence: 99%
“…As an alternative, murine reporter cells can be used. 101,102,111,112 These cells do not express BTN3A1 but require overexpression by transduction of the costimulatory molecule CD28 on the reporter cell and of counter ligands such as CD80 on the presenting cells for efficient activation. 101,102,112 Already the first report on ing away from the membrane.…”
Section: Butyrophilins Enter the Stagementioning
confidence: 99%
“…101,102,111,112 These cells do not express BTN3A1 but require overexpression by transduction of the costimulatory molecule CD28 on the reporter cell and of counter ligands such as CD80 on the presenting cells for efficient activation. 101,102,112 Already the first report on ing away from the membrane. 114 In contrast, introduction of a disulfide bridge between the C-domains, which fixes the V-conformation, diminished ABP-induced stimulation but did not affect ABP-induced mobility reduction in these BTN3A1 constructs, casting doubts on the significance of mobility changes in ABP-induced activation.…”
Section: Butyrophilins Enter the Stagementioning
confidence: 99%
“…These metabolites, such as the isopentenyl pyrophosphate (IPP), can accumulate in transformed and infected cells because of their dysregulated metabolism (127,135,137). IPP accumulates when the activity of the IPP-metabolizing enzyme farnesyldiphosphate-synthase (FPPS) is blocked (135). The use of aminobiphosphonates, such as zoledronate, inhibits FFPS, which leads to an increase in intracellular level of IPP and the activation of Vγ9Vδ2 T cells (135,(138)(139)(140).…”
Section: General Backgroundmentioning
confidence: 99%
“…IPP accumulates when the activity of the IPP-metabolizing enzyme farnesyldiphosphate-synthase (FPPS) is blocked (135). The use of aminobiphosphonates, such as zoledronate, inhibits FFPS, which leads to an increase in intracellular level of IPP and the activation of Vγ9Vδ2 T cells (135,(138)(139)(140).…”
Section: General Backgroundmentioning
confidence: 99%